Modern immigration and its relationship with motivation towards learning foreign languages. Study of Polish immigrants using English in Iceland. - Anna Karolina Szczesniak 1987- (2021)
Modern European immigration was exacerbated with the introduction of the European Freedom of Movement in 1992. This resulted in greater trans-national mobility of people and posed new challenges to migrants who had to adapt to the new surroundings, including new language reality. The following thesis aims to explore the subject of migration and its relationship to motivation towards learning foreign languages. The study was conducted in the form of a survey and it aimed to establish the tendencies in regards to learning English by Polish immigrants in Iceland. The variables were compared against each other in order to establish any existing correlation. The thesis reviews the literature available on the topic and relates it to the conducted research. It presents the data and theories about migration processes and motivation. This is followed by the description and methodology of the study as well as the results and the discussion about the findings. The results suggest that despite the lack of increase in the commitment towards learning English by Polish immigrants in Iceland the reasons behind acquiring knowledge have shifted from the integrative ones to the instrumental ones and, the perceived level of English skills has increased.